The Use of Prezi with Know, Want, and Learn (KWL) Strategy to Enhance Students Reading Comprehension - Hamid, Sitti Maryam; Rahman, Andi Qashas (Universitas Negeri Makassar, 2016)
The objectives of this research were to find out whether the use of Prezi with KWL Strategy enhances the reading comprehension and the students’ interest. This research employed quasi-experimental design. The population of this research was the first-grade students of SMAN 5 Makassar in academic 2015/2016. This research employed cluster random sampling technique. The sample consisted of 72 students which belong to two classes; 36 students in experimental class and also 36 students in control class. Research instruments were used to collect the data in this research namely reading comprehension test and questionnaire. The result of the students’ reading score in this research showed that the experimental class improved significantly from 69.69 up to 86.61. While in control class the result improved from 66.22 up to 75.89. Therefore, the significant values of Independent t-test 0.000 < α = 0.05. It means that the alternative hypothesis (H1) was accepted. Moreover, based on the students’ response on questionnaire showed that the mean score of interest was 80.61 and it was categorized as interested. Keywords: KWL Strategy, Prezi, reading comprehension, interest